2002
DOI: 10.1023/a:1021232624767
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: With a single breath perturbation, the differential Fick method can yield cardiopulmonary information using 2-3 breaths only and with a minimum of interference with the patient. Complete data analysis results in multiple determinations of the Qp and ELV values which improve the attainable precision. Our investigation points to the possibility to determine Qp, CO(Fick) and ELV also during spontaneous breathing, by using the natural tidal variations of V and P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Static lung volume, such as the end-expiratory lung volume (EELV) in ventilated patients is assessed by analyzing the concentration changes of an inert gas during wash-in/wash-out maneuvers [1-4]. A recently developed alternative to EELV is the effective lung volume (ELV), which is based on a continuous breath-by-breath analysis of the carbon dioxide after alteration of the inspiratory pattern [5]. We showed that ELV detects lung derecruitment and recruitment [6] with the additional advantage of continuous monitoring of the ventilated patient.…”
Section: Introductionmentioning
confidence: 99%
“…Static lung volume, such as the end-expiratory lung volume (EELV) in ventilated patients is assessed by analyzing the concentration changes of an inert gas during wash-in/wash-out maneuvers [1-4]. A recently developed alternative to EELV is the effective lung volume (ELV), which is based on a continuous breath-by-breath analysis of the carbon dioxide after alteration of the inspiratory pattern [5]. We showed that ELV detects lung derecruitment and recruitment [6] with the additional advantage of continuous monitoring of the ventilated patient.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before CO 2 also enters the lung tissue where it dynamically equilibrates with the alveolar concentration so that its final elimination in exhaled air, the point of measurement, can be affected by several factors such as the ventilation-perfusion balance and the tissue-to-gas ratio in the lung. The foundations of the capnodynamic method to measure EELV were first proposed by Gedeon et al by introducing small short-lasting changes in the lung’s CO 2 balance by means of brief inspiratory holds added to the breathing pattern [ 20 ]. Later, Brewer et al, described a CO 2 rebreathing method obtaining good bias and limits of agreement in a first experimental evaluation with only a small overestimation compared to a nitrogen-based method despite applying a correction factor [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…ELV, defined as the lung volume taking part into the gas exchange, was assessed as described earlier [ 39 , 40 ]. Briefly, periods of five consecutive alterations in inspiratory/expiratory ratio (1:2–1.5:1) were applied by the ventilator.…”
Section: Methodsmentioning
confidence: 99%